Active vs Passive Dictation - Mozhgan Alsadat Ghaffarzadeh Hassankiadeh (Institute of Advanced Engineering and Science, 2013)
This paper concentrates on dictation as a beneficial tool in both teaching and testing. The goal is to discuss about the points that were ignored during the years in foreign language classes. In fact this paper aims at investigating helpful techniques in reviving active dictation. Here some discussion is presented theoretically about the strategies that can be used to assist learners to develop the other skills during dictation sessions. An effective tool that can help teachers and learners during language teaching/learning processes to promote learning is dictation, if it is utilized in a proper procedure while considering all four skills in learning a foreign/second language. So the significance of the topic leads the researcher to study it. The aim is to identify the most appropriate strategies in using dictation in the classroom that may assist learners in learning a language communicatively. Therefore the current study came to existence to gain this target and to present some techniques to help in promoting such skills in language classes.DOI: http://dx.doi.org/10.11591/ijere.v2i3.1717